Political Cities. - Rogers, Dallas; Mossmann, Michael (Palgrave Macmillan, 2020)
The chapter explores the tensions between the Aboriginal context of urban development, the practices of professional planners, the participatory planning frameworks of governments and the neoliberalisation of planning governance in Australia. Rather than fitting neatly together, there are fundamental theoretical and practical tensions between Aboriginal, participatory, technocratic and neoliberal planning frameworks. Each dictates a different source of power in terms of setting the urban agenda and making planning decisions. Using the New South Wales planning system as a case study, we analyse each governance process as a discrete way of thinking about urban governance. We highlight where the political power is located to set the urban agenda and to make decisions within each of these processes. We conclude that enabling a suite of power structures in one governance space can undermine important power structures within the other governance processes.
Keywords: Stadtentwicklungsplanung; Stadtpolitik; Governance; Planungsprozess; Partizipation